An update on dual Src/Abl inhibitors. (April 2012) - Musumeci, Francesca; Schenone, Silvia; Brullo, Chiara; Botta, Maurizio
C-Src and Bcr-Abl are two cytoplasmatic tyrosine kinases (TKs) involved in the development of malignancies. In particular, Bcr-Abl is the etiologic agent of chronic myeloid leukemia, where Src is also involved; the latter is hyperactivated in several solid tumors. Because of the structural homology between Src and Abl, several compounds originally synthesized as Src inhibitors have also been shown to be Abl inhibitors, useful in overcoming the onset of some types of chronic myeloid leukemia resistances, which frequently appear in the advanced phases of pathology. In recent years, the development of such compounds has been promoted by both excellent preclinical and clinical results, and by the theory that dual or multi-targeted inhibitors might be more effective than selective inhibitors. This review is an update on the most important dual inhibitors already in clinical trials and includes information regarding compounds that have appeared in the literature in recent years.